Mineralocorticoid receptor antagonist treatment improved arterial stiffness in patients with primary aldosteronism: a cohort study compared with adrenalectomy - Che-Wei Liao; Yen-Tin Lin; Cheng-Hsuan Tsai; Yi-Yao Chang; Zheng-Wei Chen; Ching-Chu Lu; Chien-Ting Pan; Chin-Chen Chang; Bo-Ching Lee; Yu-Wei Chiu; Wei-Chieh Huang; Kuo-How Huang; et al. (SAGE Publishing, 2023)
Background: Elevated arterial stiffness in patients with primary aldosteronism (PA) can be reversed after adrenalectomy; however, the effect of medical treatment with mineralocorticoid receptor antagonist (MRAs) is unknown. Objectives: The aim of this study was to evaluate the effect of MRAs and compare both treatment strategies on arterial stiffness in PA patients. Design: Prospective cohort study. Methods: We prospectively enrolled PA patients from 2006 to 2019 who received either adrenalectomy or MRA treatment (spironolactone). We compared their baseline and 1-year post-treatment biochemistry characteristics and arterial pulse wave velocity (PWV) to verify the effects of treatment and related determinant factors. Results: A total 459 PA patients were enrolled. After 1:1 propensity score matching for age, sex and blood pressure (BP), each group had 176 patients. The major determinant factors of baseline PWV were age and baseline BP. The adrenalectomy group had greater improvements in BP, serum potassium level, plasma aldosterone concentration, and aldosterone-to-renin ratio. The MRA group had a significant improvement in PWV after 1 year of treatment (1706.2 ± 340.05 to 1613.6 ± 349.51 cm/s, p  < 0.001). There were no significant differences in post-treatment PWV ( p  = 0.173) and improvement in PWV ( p  = 0.579) between the adrenalectomy and MRA groups. The determinant factors for an improvement in PWV after treatment were hypertension duration, baseline PWV, and the decrease in BP. Conclusion: The PA patients who received medical treatment with MRAs had a significant improvement in arterial stiffness. There was no significant difference in the improvement in arterial stiffness between the two treatment strategies.